Seismic response of base isolated plan irregular structures - Volcev, Riste; Postolov, Nikola; Todorov, Koce; Lazarov, Ljupco (European Association of Earthquake Engineering (EAEE), 2018)
Nine spatial five storey structures with different type and degree of plan irregularity are analysed in this paper. The seven structures have rectangular shape, while the other two have T shape in plan. The first structure with rectangular shape is regular. Three of the remaining six structures with a rectangular base, analysed as fix supported, do not comply the condition for maximum allowed eccentricity between the centre of mass and centre of stiffness and two of the other three do not comply the condition for torsional sensitivity according to which torsional radius should be greater than the radius of gyration of the floor masses. Base isolation significantly reduces eccentricity between centre of stiffness and centre of mass of the structures with stiffness eccentricity and increases the torsional radius on each floor of torsionally sensitive structures, which leads to compliance of previously mentioned criteria. Fast nonlinear time history analysis is applied to determine the dynamic response of base isolated structures. The results obtained for the isolated rectangular structures show great reduction of the torsional effects and the interstorey drifts, compared with the corresponding fixed base structures. Fixed base structures with a rectangular shape, has 4 to 5 times larger rotations compared with the isolated. In contrast, the maximal rotations of structures with T shape occurred at base isolated models. The maximal interstorey drifts at base isolated models are about 2.5 times smaller in comparison with fixed based.
Keywords: Eurocode 8; plan irregularity; base isolation; dynamic analysis